A Single Pilot Subcarrier-Based Sampling Frequency Offset Estimation and Compensation Algorithm for Optical IMDD OFDM Systems - Zhen Zhang; Qianwu Zhang; Yingchun Li; Yingxiong Song; Junjie Zhang; Jian Chen (IEEE Photonics Journal, 2016)
A sampling frequency offset (SFO) estimation and compensation scheme for asynchronous optical intensity-modulation and direct-detection orthogonal frequency division multiplexing (OFDM) systems by using one single pilot subcarrier is proposed. Experimental demonstrations are also under taken to evaluate the performance of the mentioned scheme, and results show that precise SFO estimation with an accuracy of < ±0.2 ppm can be achieved under the SFO range from −1000 to 1000 ppm after 25 km standard single mode fiber (SSMF) transmission. Meanwhile, an SFO compensation method by extending the channel response with the phase shift correction term is also presented; more than 1000 and 400 ppm SFO effects can be compensated by using the phase shift correction term and its approximation, respectively.